Leishmaniose visceral : aspectos relacionados à clínica, diagnóstico, epidemiologia e vigilância em um foco urbano emergente brasileiro - Luz, João Gabriel Guimarães (2020)
This research attempted to evaluate aspects related to the clinic, diagnosis, epidemiology, and surveillance of visceral leishmaniasis (VL) in the urban area of the Brazilian municipality of Rondonópolis, Mato Grosso State. All 81 autochthonous human VL cases reported between 2011 and 2016 were included. Clinical, diagnostic, and epidemiological aspects recorded from notification forms were described. A matched case-control study was also conducted to determine the socioeconomic, environmental, and daily habits associated with the occurrence of human VL at the individual level. Human cases were georreferenced and the incidence of the disease was calculated for each neighborhoods of the municipality. In sequence, spatial analysis for point patterns and for the incidence at the neighborhood level were performed. The spatial correlation between smoothed human VL incidence and canine VL seropositivity rates per neighborhood was also checked. In addition, passive surveillance of domestic canine reservoirs was explored by determining the factors associated with canine VL diagnosis-seeking behavior. In parallel, we analyzed the profiles of dog owners and their animals screened on free demand. Human VL incidence decreased over the study period. The lethality rate was 8.6% overall, but ranged widely and peaked in 2016. Almost 10.0% of patients had VL/HIV coinfection. The occurrence of VL prevailed among men, brown-skinned and aged 0-4 years. Lower age was the main difference among the total VL cases and those who were coinfected or died. Fever, weakness, and splenomegaly were most frequent clinical manifestations. Bacterial infections and bleeding were associated with death due to VL. The majority of VL cases were reported by hospitals. The patients mainly sought primary health care centers at the onset of symptoms. However, they had to visit seven health services on average to achieve a confirmed diagnosis, which were conducted mainly using serology. The time from the onset of symptoms to the diagnosis of VL was longer among adult patients and directly correlated with the patient’s age. The variables associated with VL occurrence were the outdoor location of a bathroom and/or kitchen separated from the rest of the house, the presence of a vegetable garden and the presence of decaying fruits in the backyard. Human VL cases demonstrated a heterogeneous, clustered, and periphery pattern. Neighborhoods within a spatial low-risk cluster presented higher mean income, literacy rate, and sanitary sewage service coverage when compared to the rest of the municipality. A positive spatial correlation was found between the occurrence of human and canine VL, locally in the northern outskirt. Passive surveillance of domestic dogs increased over years with high seropositivity rates. It was observed that a decrease in the distance to the screening site, as well as an increase in the canine VL seropositivity, were strongly associated with an increase in canine VL diagnosis seeking- behavior. Apparently, this practice was related to dog owners with better socioeconomic status and animals with suggestive clinical manifestations of canine VL. These findings may support a better understanding of the dynamics of VL occurrence, and a better guiding for surveillance and control in endemic areas.